Psychometric evaluation of the characteristics of delusions rating scale as an expert rating scale - Senger, Nana Christina; Büche, Liesa; Bock, Anique von; Rückl, Sarah; Marx, Jens Thorsten; Kaiser, Stephan; Barthel, Andreas; Vedder, Helmut; Mundt, Christoph; Kronmüller, Klaus-Thomas (Psychopathology, 2010)
Background: Research suggests delusions may be better viewed as multidimensional rather than dichotomous phenomena. The aim of this study was to assess the reliability and validity of a German version of the Characteristics of Delusions Rating Scale (CDRS) as an expert rating scale. Method: 200 inpatients with schizophrenic spectrum and affective disorders with delusions were assessed with the CDRS and other delusion rating scales. Factorial validity was analysed, and differences between diagnostic groups on the CDRS subscales as well as on the total score were examined. Results: The CDRS was found to have good inter-rater reliability and internal consistency as an expert rating. Factor analysis yielded an interpretable structure with 3 factors - cognition, emotion and bizarreness - accounting for 70% of the variance. The convergent and differential validity of the scales was supported. Compared to other scales, the CDRS measures all dimensions of delusional experience that have been suggested to date with the exception of behavioural aspects. Conclusions: The results support the view of delusions as multidimensional phenomena. The CDRS as an expert rating is a reliable and valid assessment tool for dimensions of delusional experience and an economical instrument for research and clinical practice. Further research is needed to examine the dimensional structure underlying delusional phenomena and the relationship of the dimensions to neurobiological and psychotherapeutic processes.
Gesehen am 27.02.2023